2017
DOI: 10.1128/mcb.00408-16
|View full text |Cite
|
Sign up to set email alerts
|

Predicted RNA Binding Proteins Pes4 and Mip6 Regulate mRNA Levels, Translation, and Localization during Sporulation in Budding Yeast

Abstract: In response to starvation, diploid cells of undergo meiosis and form haploid spores, a process collectively referred to as sporulation. The differentiation into spores requires extensive changes in gene expression. The transcriptional activator Ndt80 is a central regulator of this process, which controls many genes essential for sporulation. Ndt80 induces ∼300 genes coordinately during meiotic prophase, but different mRNAs within the regulon are translated at different times during sporulation. The protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…To gain insights into the cellular role of Mip6, we investigated whether Mip6, similar to Mex67, shuttles between the nucleus and the cytoplasm. Unfortunately for the purpose of such analysis, an endogenous Mip6‐GFP protein was undetectable by confocal microscopy, probably due to its low abundancy . We therefore expressed Mip6 under the control of the ADH1 promoter ( ADH1 pr) either as a plasmid (p‐ ADH1 pr‐Mip6‐GFP) or at its genomic locus (g‐ ADH1 pr‐Mip6‐GFP), both of which resulted in increased Mip6 expression levels (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the cellular role of Mip6, we investigated whether Mip6, similar to Mex67, shuttles between the nucleus and the cytoplasm. Unfortunately for the purpose of such analysis, an endogenous Mip6‐GFP protein was undetectable by confocal microscopy, probably due to its low abundancy . We therefore expressed Mip6 under the control of the ADH1 promoter ( ADH1 pr) either as a plasmid (p‐ ADH1 pr‐Mip6‐GFP) or at its genomic locus (g‐ ADH1 pr‐Mip6‐GFP), both of which resulted in increased Mip6 expression levels (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…Another study that dealt with both Mip6 and Pes4 also suggested a role for Mip6 in regulating steady state expression, protection, and mRNA localization during stress conditions (Jin et al, 2017). They also found that during stress induced sporulation, Mip6 localizes to cytoplasmic foci that contained mRNA transcripts which Mip6 protected from degradation.…”
Section: Mip6 Additional Role During Cellular Stressmentioning
confidence: 93%
“…Although both had a role during cellular stress induced sporulation (Jin et al, 2017), and both re-localize to cytoplasmic foci, however each protein displayed distinct cytoplasmic protein localization. Moreover, while the protection for few mRNA transcripts by either Mip6 or Pes4 during sporulation was redundant, many mRNA transcripts were uniquely protected by either Mip6 or Pes4.…”
Section: Pes4 Evolutionary Divergence Of Functionmentioning
confidence: 98%
See 2 more Smart Citations